Frictionless Technology Diffusion: The Case of Tractors - Manuelli, Rodolfo E.; Seshadri, Ananth (American Economic Review, 2014)
Empirical evidence suggests that there is a long lag between the time a new technology is introduced and the time at which it is widely adopted. The conventional wisdom is that these observations are inconsistent with the predictions of the frictionless neoclassical model. In this paper we show this to be incorrect. Once the appropriate driving forces are taken into account, the neoclassical model can account for 'slow' adoption. We illustrate this by developing an industry model to study the equilibrium rate of diffusion of tractors in the U.S. between